Tobacco use patterns among women in reproductive age group: a cross sectional study in the rural area of Belgaum district, Karnataka, South India - Kulkarni, Namratha; Havaldar, Pavan P.; Naik, Vijaya A. (International Journal Of Community Medicine And Public Health, 2019)
Background: Tobacco imposes a colossal burden of disease and death leading to catastrophic health, social, economic, and environmental effects. “Tobacco” kills both men and women but sex-specific differences exist. Traditional forms of tobacco like dentifrice or tobacco tooth powder and betel quid, tobacco and lime mixture are commonly used and also, the new products use is increasing not only among men but even among children, teenagers, women of reproductive age. This study was done to know the patterns and other correlates of tobacco use among the rural women in the reproductive age group. Methods: A community based cross sectional study, conducted from January 2011 to December 2011 among 1200 rural women aged between 15 years to 49 years residing in primary health centre, Vantmuri area, Belgaum, Karnataka, India. Statistical analysis was done using rates, ratios and chi-square tests. Results: Tobacco consumption was seen in 9.7% of the study participants. A very high percentage of 79 (67.5%) had more than 10 years of exposure to tobacco amongst the users. Dentifrice was the most common form of tobacco used (85.5%) followed by 32 (27.4%) plain tobacco consumption. However, 49 (4.1%) consumed multiple forms of tobacco, most common being dentifrice along with plain tobacco or paan with beetelquid or used snuff. Conclusions: The distribution of tobacco consumption is likely to maintain, and perhaps increase, the current considerable socioeconomic differentials in health in India. Dual users are at much higher health risks than those who consume the individual tobacco product. It also emphasizes the variations in patterns of using tobacco among rural women. There is a need for periodical surveys using more consistent definitions of tobacco use and eliciting information on different types of tobacco consumed.